ANALISIS KONTRAK BERBASIS KINERJA (KBK) DAN KONTRAK KONVENSIONAL STUDI KASUS: PROYEK PEMBANGUNAN JALAN KBK SEMARANG-BAWEN DAN PROYEK PEMBANGUNAN JALAN TOL SEMARANG-SOLO - Indra Wijaya; Vanessa Nurmalita; M. Agung Wibowo; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2014)
Construction sector in Indonesia, especially for road construction projects are progressing very rapidly in recent years. Indonesia is intensively implementing the road construction project, from new road construction, road maintenance and repairs. Road construction sector in Indonesia is mostly using the conventional contract system, with a lump sum or unit price. In this conventional contract service user must fully bear the risks associated with the quality of work that is to be maintained. It required an innovative method in order to contract the service user and the service provider can be better off, for example with the system performance based contracting (PBC). This study will analyze the differences between the PBC system and conventional system by comparing the life cycle project, project coordination line, the construction, the maintenance period, and the budget plan contract. The research method used was a descriptive analytical methods and data collection through direct field observations and interviews with project case studies Construction Project Semarang-Bawen Road with PBC and Construction Project Semarang-Solo Highway. From the results, the fact that the PBC has a single stage system that is not present in the conventional contract there is system maintenance services. At  the PBC system imposed fines ranging from construction period while the conventional system of fines awarded the contract if the contract or is unable to complete the construction work by the duration of time that has been given. At the PBC system there is not planning consultant contracts while the conventional system, there are consultants planning consultant. At the PBC system maintenance is faster than the conventional contract system maintenance. The budget plan contract at the PBC system is higher than the conventional contract system’s budget plan contract.